Islam, politics and change : the Indonesian experience after the fall of Suharto - Dijk, C. van (Cornelis), 1946-; Kaptein, N. J. G. (Debates on Islam and society., 2016)
In this book researchers investigate what happened after violent protests all over the country had forced President Suharto to step down in 1998 and Indonesia successfully made the transition from an authoritarian state to a democracy. This title was made Open Access by libraries from around the world through Knowledge Unlatched.